Ammonifying and phosphorus-solubilizing function of Aliikangiella maris sp. nov. isolated from Phaeocystis globosa bloom and algal–bacterial interactions - Li, Fei; Xu, Ming-Ben; Pan, Liang-Hao; Li, Jie; Lan, Cai-Bi; Li, Zhe; Lu, Shan; Lai, Jun-Xiang; Li, Peng-Fu (Frontiers in Microbiology, 2025)
Phaeocystis globosa blooms are of escalating global concern due to their substantial ecological impacts on marine ecosystems. Emerging evidence indicates that algae–bacterial interactions play pivotal roles in shaping the ecology and evolution of harmful algal blooms, although much of this interplay remains unexplored. We successfully isolated and propagated two novel bacterial strains from Phaeocystis globosa bloom. Two novel Gram-negative, non-spore-forming, motile, rod-shaped, and yellow-pigmented bacteria were designated strains GXAS 306T and GXAS 311. According to phenotypic, chemotaxonomic, phylogenomic, and comparative genomic analyses data, strains GXAS 306T and GXAS 311 were considered to represent a novel species of the genus Aliikangiella. Genomic analysis revealed that strain GXAS 306T had many potential functions favorable for interacting with algae, and further experimental evidence confirmed the ammonifying and phosphorus-solubilizing function. Co-culture experiments showed that strain GXAS 306T significantly improved algal growth parameters of two typical P. globosa strains (Pg293 and PgV01), particularly under nitrogen or phosphorus deficiency. Specifically, cell densities were observed to increase by 19.6–86.0%, accompanied by substantial enhancements in photosynthetic performance with increases of 8.0–30.6% in Fv/Fm and 10.9–27.9% in rETRmax. Overall, these results shed light on intricate relationships between P. globosa and its associated bacterial partners, which may influence the growth characteristics of algae.